A Polymer/Carbon‐Nanotube Ink as a Boron‐Dopant/Inorganic‐Passivation Free Carrier Selective Contact for Silicon Solar Cells with over 21% Efficiency. (12th July 2020) - Chen, Jianhui; Wan, Lu; Li, Han; Yan, Jun; Ma, Jikui; Sun, Biao; Li, Feng; Flavel, Benjamin S.
Abstract: Traditional silicon solar cells extract holes and achieve interface passivation with the use of a boron dopant and dielectric thin films such as silicon oxide or hydrogenated amorphous silicon. Without these two key components, few technologies have realized power conversion efficiencies above 20%. Here, a carbon nanotube ink is spin coated directly onto a silicon wafer to serve simultaneously as a hole extraction layer, but also to passivate interfacial defects. This enables a low‐cost fabrication process that is absent of vacuum equipment and high‐temperatures. Power conversion efficiencies of 21.4% on an device area of 4.8 cm 2 and 20% on an industrial size (245.71 cm 2 ) wafer are obtained. Additionally, the high quality of this passivated carrier selective contact affords a fill factor of 82%, which is a record for silicon solar cells with dopant‐free contacts. The combination of low‐dimensional materials with an organic passivation is a new strategy to high performance photovoltaics. Abstract : A carbon nanotube ink is developed that can be spin coated directly onto a silicon wafer and which serves as a hole extraction layer but also to passivate interfacial defects. Power conversion efficiencies of 21.4% on a device area of 4.8 cm 2 and 20% on an industrial size (245.71 cm 2 ) wafer are obtained.